2009
DOI: 10.1177/147323000903700533
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Thickness in Patients with Age-Related Macular Degeneration

Abstract: This observational study was designed to compare corneal thickness in patients with age-related macular degeneration (AMD) with the thickness in healthy control subjects to determine if there is a correlation between corneal thickness and the development of AMD. A total of 69 patients (119 eyes) with AMD and 31 healthy subjects (56 eyes) were evaluated. Corneal thickness was measured with a Galilei Dual Scheimpflug Analyser and retinal thickness was measured using optical coherence tomography. There was no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Pair comparisons for the day before cataract surgery and 3 months after surgery for minimum foveal macular thickness and macular thickness in the fovea and eight perifoveal areas (n = 23 for all comparisons) N Knez, K Šiško, D Pahor Reversible postsurgical changes to macular thickness changes can be identified with OCT, a diagnostic method that represents a completely new approach to retinal choroidea evaluation. 26 OCT is simple, objective, non-contact, reproducible and normally well tolerated by patients.…”
Section: Tablementioning
confidence: 99%
“…Pair comparisons for the day before cataract surgery and 3 months after surgery for minimum foveal macular thickness and macular thickness in the fovea and eight perifoveal areas (n = 23 for all comparisons) N Knez, K Šiško, D Pahor Reversible postsurgical changes to macular thickness changes can be identified with OCT, a diagnostic method that represents a completely new approach to retinal choroidea evaluation. 26 OCT is simple, objective, non-contact, reproducible and normally well tolerated by patients.…”
Section: Tablementioning
confidence: 99%
“…In the first study, Kymionis et al (9) compared the CCT of healthy subjects with the CCT of patients who had AMD by using ultrasound pachymeter, and did not find a statistically significant difference between these groups. A similar study done by using Scheimpflug camera did not reveal a statistically significant difference between CCT of healthy individuals and CCT of patients with AMD (10). These 2 previous studies can be valuable with regard to providing contributions to explain the pathophysiologic mechanism of AMD.…”
Section: Discussionmentioning
confidence: 69%
“…In the literature, 2 studies can be found that investigate the relationship between CCT and neovascular AMD by comparing the eyes of different subjects (9, 10). However, it is well known that numerous factors like cardiovascular-related factors, behavioral and lifestyle factors, genetic factors, hormonal factors, and inflammatory factors can affect the development of AMD (11-12-13-14-15).…”
Section: Introductionmentioning
confidence: 99%